Cost pass-through in strategic oligopoly: Sectoral evidence for the EU ETS - Victoria Alexeeva-Talebi (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
Price adjustments, particularly the cost pass-through relationships, are at the core of the analysis on how asymmetric climate change policy initiates two channels of carbon leakage: (decreasing) market shares and profit margins. Using advanced time-series techniques, this paper explores the pass-through relationships in an oligopoly setting. Under the condition of oligopolistic competition with strategic interactions, the cost pass-through of domestic firms is restricted by strategic interactions with foreign competitors. The empirical section demonstrates that strategic pricing in the presence of the incomplete cost pass-through is by far the prevailing behaviour of German energy-intensive sectors participating in the EU Emissions Trading Scheme (ETS). The relatively low cost pass-through rates in the long-run in most sectors in our sample - in comparison to studies which do not account for strategic interactions - are consistent with earlier findings. Additional costs induced by the EU ETS are therefore likely to be absorbed through a reduction of profit margin, creating incentives to relocate business abroad. Policy implications of the results are that strategic interactions between domestic and foreign firms could be a critical factor in applying offsetting instruments to address carbon leakage domestically. Accounting for oligopolistic structures - with and without strategic interactions - should therefore be a central issue within the broader context of how market structure affects climate change policies.
Keywords: F18; C22; L11; 330; cost pass-through; strategic oligopoly; emissions trading scheme; Emissionshandel; Umweltschutzkosten; Betriebliche Preispolitik; Verarbeitendes Gewerbe; Marktmacht; Internationaler Wettbewerb; Oligopol; Schätzung; Deutschland